Pedagogy or Personal Qualities? University Students’ Perceptions of Teaching Quality - Tuomainen, Satu (American Journal of Education and Learning, 2019)
Teaching quality is a term used to express the level of teaching practices, methods, content and delivery but can also be understood subjectively by the audiences involved, the students. The aim of this phenomenographic study was to explore international master’s students’ (N=15) perceptions of teaching quality while studying at university in Finland. The students were interviewed about their perceptions and experiences of teaching quality according to a phenomenographic research approach. Three main themes arose from the interview data: teaching quality as pedagogical professionalism, teaching quality as the personal qualities of the teacher, and teaching quality as the overall learning environment. These themes included eight distinctive categories: knowledge and expertise of the teacher, engaging and inspiring, clarity of purpose and delivery, connection with students, approachability, relevant course contents, physical learning environment and role of the students. The results support previous studies on higher education teaching quality through the significance of expertise, connection with students and activating teaching methods. While the results mainly mirror previous studies on this subject, new perceptions such as the role of research and the role of the learning environment introduce new aspects to the phenomenon. Teaching quality was also perceived through negative experiences which indicates a need to further develop university teaching practices and to increase pedagogical training for university teaching staff.